OPERASI GABUNGAN, JOIN, KOMPOSISI DAN HASIL KALI KARTESIAN PADA GRAF FUZZY SERTA KOMPLEMENNYA - Novia, Tina Anggitta; Ratnasari, Lucia (MATEMATIKA, 2010)
A fuzzy graphs is a nonempty set together with a pair function and satisfied This paper described about some operations on fuzzy graphs such as union, join, compositions and cartesian product. Complement of union two fuzzy graphs is join of their complement, join complement of two fuzzy graphs is union their complement. Complement of composition two strong fuzzy graphs is composition of their complement, but complement of cartesian product two stong fuzzy graphs is need not cartesian product of their complement.